2021
DOI: 10.1007/s10554-021-02246-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between myocardial mechanical dispersion and ventricular arrhythmogenicity in chagas cardiomyopathy

Abstract: Endemic Chagas diseaseis a major health concernin LatinAmerica. Ventricular arrhythmias (VA) is a hallmark of Chagas cardiomyopathy (ChC) associated with worse prognosis. To verify if there is an association between myocardial mechanical dispersion and ventricular arrhythmogenicity in CCM. This is a cross-sectional study involving 77 patients with CCM. Global longitudinal strain (GLS) and MD were evaluated by echocardiogram, derived from the speckle tracking technique. Myocardial MD was measured from the onset… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(40 reference statements)
0
1
0
1
Order By: Relevance
“…GLS reflects the longitudinal deformation of the myocardium in a more sensitive and reproducible way than LVEF. 37,38 Azevedo et al 39 demonstrated a significant association between GLS and myocardial mechanical dispersion with nonsustained ventricular tachycardia in 77 patients with CCC. Recently, reductions in GLS were also observed in the undetermined form of the disease, before the onset of fibrosis.…”
Section: Brito Et Al Denervation Hypoperfusion Fibrosis In CCCmentioning
confidence: 99%
“…GLS reflects the longitudinal deformation of the myocardium in a more sensitive and reproducible way than LVEF. 37,38 Azevedo et al 39 demonstrated a significant association between GLS and myocardial mechanical dispersion with nonsustained ventricular tachycardia in 77 patients with CCC. Recently, reductions in GLS were also observed in the undetermined form of the disease, before the onset of fibrosis.…”
Section: Brito Et Al Denervation Hypoperfusion Fibrosis In CCCmentioning
confidence: 99%
“…O GLS reflete a deformação longitudinal do miocárdio de forma mais sensível e reprodutível do FEVE. 37,38 Azevedo et al 39 demonstraram uma associação significativa entre GLS e dispersão mecânica miocárdica com a taquicardia ventricular não sustentada em 77 pacientes com CCC. Recentemente, também foi observada a redução do GLS ainda na forma indeterminada da doença, antes do surgimento de fibrose.…”
Section: Brito Et Al Denervação Hipoperfusão Fibrose Na CCCunclassified